Scooby-Doo! : locura en el museo - McCann, Jesse Leon.; Geada, Karina; Duendes Del Sur (Firm) (New York : Scholastic, 2010)
To celebrate the newest exhibit the Coolsville Museum is hosting a party, but an uninvited guest shows up--the mummy from the cursed treasure wants his revenge.
Keywords: Mummies -- Juvenile fiction; Egyptians -- Juvenile fiction; Museums -- Juvenile fiction; Dogs -- Juvenile fiction; Mystery and detective stories -- Juvenile fiction